Chronic obstructive pulmonary disease related to wood smoke and impact of the combined exposure to tobacco - C.A. Torres-Duque; C. Jaramillo; A. Caballero; N.J. Proaños-Jurado; M.J. Pareja-Zabala; J.B. Soriano; M. González-García (IJTLD Open)
BACKGROUND: Global Initiative for Chronic Obstructive Lung Disease (GOLD) 2023 highlights the need to explore aetiotypes of chronic obstructive pulmonary disease (COPD) beyond the tobacco-smoking COPD. Exposure to wood smoke (WS) is a risk factor for COPD in women, but the effect of the combined exposure to tobacco smoke (TS) in the general population and among COPD patients, and the characteristics of WS-COPD are unclear. METHOD: This was an analysis of data from PREPOCOL (Prevalence of COPD in Five Colombian Cities Situated at Low, Medium, and High Altitude), a random cross-sectional population-based study (n = 5,539) focusing on the effect of combined WS and TS exposure and WS-COPD characterisation. RESULTS: Prevalence of COPD was significantly higher in those exposed to both WS and TS (16.0%) than in those exposed to WS (6.7%) or TS (7.8%) only (P < 0.001). Exposure to WS was associated with COPD in men (OR 1.53, P = 0.017). WS-COPD individuals were more frequently female, older, shorter and had higher forced expiratory volume in 1 sec (FEV1) (all P < 0.05). Those exposed to both WS and TS had more symptoms and worse airflow limitation (P < 0.001). CONCLUSION: This was the first random population-based study showing that WS is an associated risk factor for COPD also in men, and that people exposed to both WS and TS have a significantly higher prevalence of COPD. Similarly, COPD subjects exposed to both types of smoke have more symptoms and greater airflow obstruction. This suggests an additive effect of WS and TS.